Food security indicators after humanitarian interventions including food aid in Zimbabwe - Gandure, Sithabiso; Drimie, Scott; Faber, Mieke (SAGE Publications, 2010)
Rural households in contemporary Zimbabwe experience various levels of food insecurity and vulnerability. Worsening macroeconomic conditions, a fragile political environment, poor rainfall, low incomes, deteriorating environmental conditions, and the impact of HIV and AIDS characterize their livelihoods. Non-governmental organizations have responded to the situation through a number of food interventions to alleviate food insecurity and poverty.To provide an analysis of food security indicators used to assess households benefiting from food interventions in 2006 in Zimbabwe.A total of 60 households were chosen for each of three districts (Uzumba-Maramba-Pfungwe [UMP], Chivi, and Tsholotsho), targeting beneficiaries of the Agricultural Protracted Relief Programme. Household food security indicators calculated on the basis of data collected by questionnaire included the Household Dietary Diversity Score (HDDS), months of food shortages, and the Household Food Insecurity Access Scale (HFIAS). Districts were compared by analysis of variance and Tukey post hoc analysis.The mean HDDS differed between the districts; households in Chivi consumed foods from a greater variety of groups than households in Tsholotsho and UMP (4.7 vs. 2.7 and 3.0, respectively; p < .001). Food shortages during the previous year were experienced by 76.4% of the households, with UMP having the lowest occurrence of food shortages (56.7%) and Tsholotsho the highest (95%). Households in Tsholotsho experienced hunger throughout the year; for households in UMP and Chivi, October to January were the critical months when households experienced the most hunger. Spearman correlation analysis showed an inverse correlation between HFIAS and HDDS ( r = −0.425, p < .01). Households that experienced food shortages the previous year had a lower mean HDDS (3.2 vs.3.9, p = .013) and a higher mean HFIAS (17.1 vs. 12.0, p < .001) than households that did not experience food shortages.The study demonstrated the value of using a variety and combination of indicators in the design of food security interventions. The HDDS showed that beyond availability, food security also involves access to a variety of nutritious foods. The indicator pertaining to months of food shortages allows a deeper understanding of the nature of food insecurity; hunger in Tsholotsho is experienced throughout the year, implying that the causes are chronic rather than seasonal, whereas Chivi and UMP experience seasonal hunger. The HFIAS usefully revealed the condition of food security in each site in terms of the availability, stability, and intake of food.